(untitled) (Bangladesh Journal of Zoology, 2018)
A study on the orb-weaving spider genus Eriovixia Archer was carried out from different areas of Bangladesh. Two species of the genus were recorded of which one species E. nocturnalis nov. sp. is reported to be new to science and another one E. laglaizei (Simon) is a new record for the area of present study. The paper contains generic diagnosis, illustrated description, distribution and key to the species. Bangladesh J. Zool. 46(1): 1-10, 2018